Holmium-166 Radioembolization of Hepatic Metastases in Salvage Setting: Preliminary Findings from a Single Center Experience - Murat Dökdök; Kezban Berberoğlu (Journal of Clinical Interventional Radiology ISVIR)
Purpose The aim of this study is to report the early outcomes of holmium-166 (166Ho) radioembolization in the treatment of liver metastases.